HOTS-BASED ASSESSMENT: THE STORY OF ENGLISH TEACHER’S KNOWLEDGE, BELIEFS, AND PRACTICES - Handayani, Anis; Sari, Septhina Shinta; Sumardi, Sumardi (Pusat Pengembangan Bahasa IAIN Tulungagung, 2019)
High-Order Thinking skills have been a trend in recent years. Researchers studied on aspects of HOTS. Some studied on how to teach it to students while some are on how to assess it. However, the implementation of HOTS is strongly affected by the teacher?s beliefs ?including knowledge, beliefs, and practices (Borg, 2001). The present study analyzes the teacher?s beliefs on HOTS-based assessment. It uses narrative inquiry as the research method. The data are gotten from the participant?s interview and document analysis ?test items constructed by the participant. The data are then analyzed using short story analysis. The results show that the participants occupied the knowledge of HOTS-based assessment mainly through independent study. She believes that HOTS-based assessment can be applied in High School level. Furthermore, it gives benefits for the students. She practices HOTS-based assessment in her class by constructing HOTS items. However, some English teachers have not implemented it in their class.